Efektivitas Implementasi Sistem Informasi Manajemen Keuangan Daerah di Kabupaten Semarang - Arjun Riyadi; Dyah Palupiningtyas (Universitas Sains dan Teknologi Komputer, 2024)
The study investigates the efficacy of implementing the Regional Financial Management Information System (SIMKD) in Semarang Regency. Utilizing a qualitative methodology, findings reveal suboptimal effectiveness in SIMKD implementation. Factors influencing this include human resource competency, information technology infrastructure availability, leadership engagement, and organizational culture. Proposed strategies to enhance SIMKD effectiveness encompass developing human resources, fortifying IT infrastructure, fostering leadership commitment, and nurturing a performance-driven organizational ethos. This research contributes theoretically and practically toward optimizing SIMKD utilization for more efficient, transparent, accountable, and effective regional financial administration.